INFLUENCE OF COUMARIN ON PRODUCTIVITY, IMMUNITY AND ANTIOXIDANT STATUS OF HEALTHY BROILERS - Galimzhan K. Duskaev; Tatyana A. Klimova (Siberian Journal of Life Sciences and Agriculture, 2023)
Background. Coumarins are natural compounds (secondary metabolites of plant origin) that have a wide range of biological activity, mainly due to their ability to interact with various enzymes and receptors in living organisms. The relevance of their use in feeding poultry is obvious, in view of the active search for alternatives to feed antibiotics.